Bushen-Yizhi Formula Alleviates Neuroinflammation via Inhibiting NLRP3 Inflammasome Activation in a Mouse Model of Parkinson's Disease. (26th August 2018) - Mo, Yousheng; Xu, Erjin; Wei, Renrong; Le, Baoluu; Song, Lei; Li, Dongli; Chen, Yonggen; Ji, Xiaotian; Fang, Shuhuan; Shen, Jiangang; Yang, Cong; Wang, Qi
Abstract : Parkinson's disease (PD), the second most common neurodegenerative disease, is characterized by the progressive loss of dopaminergic neurons in the substantia nigra. Although the molecular mechanisms underlying dopaminergic neuronal degeneration in PD remain unclear, neuroinflammation is considered as the vital mediator in the pathogenesis and progression of PD. Bushen-Yizhi Formula (BSYZ), a traditional Chinese medicine, has been demonstrated to exert antineuroinflammation in our previous studies. However, it remains unclear whether BSYZ is effective for PD. Here, we sought to assess the neuroprotective effects and explore the underlying mechanisms of BSYZ in a 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine- (MPTP-) induced mouse model of PD. Our results indicate that BSYZ significantly alleviates the motor impairments and dopaminergic neuron degeneration of MPTP-treated mice. Furthermore, BSYZ remarkably attenuates microglia activation, inhibits NLPR3 activation, and decreases the levels of inflammatory cytokines in MPTP-induced mouse brain. Also, BSYZ inhibits NLRP3 activation and interleukin-1 β production of the 1-methyl-4-phenyl-pyridinium (MPP + ) stimulated BV-2 microglia cells. Taken together, our results indicate that BSYZ alleviates MPTP-induced neuroinflammation probably via inhibiting NLRP3 inflammasome activation in microglia. Collectively, BSYZ may be a potential therapeutic agent for PD and the related neurodegeneration diseases.